The Impact of the Agrarian Reform on the cargo system - Gow, David D. (1973)
In this article we intend to examine the changes suffered by one of the traditional institutions of the Andean Regions, the cargo system, with the application of the Agrarian Reform. A study of this type is not only of theoretical but of empirical interest because the current Government of Peru is causing a change in the rural parts of the country with the application of the Agrarian Reform Law and the establishment of production cooperatives. One of the purposes of Law No. 17716, the Agrarian Reform Law, is to promote market integration and expand the purchasing power of the peasant groups with the lowest incomes (Carrol: 1970, pp. 29-30 and Mann , 1970). If the Agrarian Reform tends to increase the economic resources of the peasants, we wonder if the higher income they have will be spent in the market or will serve to make the sumptuousness of the festivities.